2014 IEEE International Conference on Automation Science and Engineering (CASE) 2014
DOI: 10.1109/coase.2014.6899384
|View full text |Cite
|
Sign up to set email alerts
|

Predicting patient risk of readmission with frailty models in the Department of Veteran Affairs

Abstract: Abstract-Reducing potentially preventable readmissions has been identified as an important issue for decreasing Medicare costs and improving quality of care provided by hospitals. Based on previous research by medical professionals, preventable readmissions are caused by such factors as flawed patient discharging process, inadequate follow-ups after discharging, and noncompliance of patients on discharging and follow up instructions. It is also found that the risk of preventable readmission also may relate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It concluded that trying to elongate the gap between hospitalizations should be an essential goal for evaluating the quality of treatment. Ajorlou et al (2014) proposed a risk prediction model based on hierarchical nonlinear mixed effect to recognize patients with high likelihood of discharging, non-compliances to decrease Medicare costs and improve quality of care provided by hospitals. It applied stepwise variable selection in the mixed-effect framework and extended the (typical) random frailty model for Weibull hazard function with incorporated patient factors.…”
Section: Search Strategy and Inclusion Criteriamentioning
confidence: 99%
“…It concluded that trying to elongate the gap between hospitalizations should be an essential goal for evaluating the quality of treatment. Ajorlou et al (2014) proposed a risk prediction model based on hierarchical nonlinear mixed effect to recognize patients with high likelihood of discharging, non-compliances to decrease Medicare costs and improve quality of care provided by hospitals. It applied stepwise variable selection in the mixed-effect framework and extended the (typical) random frailty model for Weibull hazard function with incorporated patient factors.…”
Section: Search Strategy and Inclusion Criteriamentioning
confidence: 99%